The effect of IFRS implementation on earnings quality and corporate value (an empirical study on go public manufacturing companies) - Gunasti Hudiwinarsih (The Indonesian Accounting Review, 2014)
IFRS Implementation on Earnings Quality and Corporate Value needs to be paid attention. This is due to the fact that in the era of globalization, the companies require an international accounting system that can be applied internationally in every country, or a necessary harmonization of international accounting standard in order to produce comparable financial information, ease in conducting competitive analysis and good relationship with customers, suppliers, investors, and creditors. The purpose of this research is to obtain empirical evidence on the effect of IFRS implementation on earnings quality and corporate value. The samples used are manufacturing companies listed on the Indonesia Stock Exchange, during the period of one year before the implementationof IFRS and one year after the implementation of IFRS. The results ofthis study indicate that there are differences in earnings quality and corporate value, either after or before the implementation of IFRS. IFRS can provide quality reporting and better business environment.